Identifying the Early Warnings of Currency Crisis in India. Issue 4 (November 2019) - Mohana Rao, Balaga; Padhi, Puja
We empirically investigate the recent history of currency crises (stress periods) and the factors influencing their likelihood in India. This study aims at constructing an early warning system (EWS) to forecast the possibility of an imminent crisis in the crisis window of 12 months by employing signal extraction methodology and logistic regression model for the period 1986–2015. Among the 22 identified crisis months (stress periods), only early episodes (1990–1991) were followed by a devaluation and not the later periods (post 1991). Both signal extraction methodology and logistic regression model indicate no relative importance to the three generations of currency crises models. Nevertheless, the results advocate that logistic regression model fares better than signal extraction technique. The results also suggest that building an EWS can be an effective diagnostic technique. JEL Codes: F31, F47, G01